ANALISIS TINGKAT KUNJUNGAN KEMBALI KONSUMEN PADA LOCAL COFFEE SHOP DI KOTA BATAM - Putra, Edy Yulianto (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
This study aims to find the relationship between several variables that affect the level of return visits to the local coffee shop in Batam, including the variable perception of product quality, service, eWOM, trust, and also the experience felt by consumers. The construction of hypotheses and their framework is based on previous researchers who really focus on the level of return visits, so researchers add relationships that have not been previously studied and also with the hope of providing more varied and accurate results. The hope of this research in the future is aimed at increasing return visits to local coffee shops in Batam City, and is also expected to improve the local economy of entrepreneurs in the field, then also be able to provide answers to entrepreneurs to realize what are the concerns of consumers in determining the level of a return visit.